2016
DOI: 10.17221/66/2014-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Root rot and damping-off of Aleppo pine seedlings caused by Pythium spp. in Algerian forest nurseries

Abstract: Aleppo pine (Pinus halepensis Miller) is a common forest tree in the Mediterranean Region. Production of Aleppo pine seedlings is hindered by damping off and root rot diseases in cooler conditions of north-western Algeria, which significantly reduces the seedling emergence. is work was carried out to evaluate the pathogenicity of different Pythium Pringsheim species on Aleppo pine seedlings. Seventeen isolates of Pythium spp. were isolated from diseased seedlings, identified to the species level based on DNA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Specifically, in Algeria, the most injurious fungus species affecting palms are Fusarium oxysporum, the causal agent of ‘bayoud’, or Fusarium wilt [ 92 , 93 ], and Thielaviopsis paradoxa , the agent of the black scorch disease [ 94 , 95 ]. Different species of the genus Fusarium also affect cereals [ 2 , 96 ], forest trees (Aleppo Pine) [ 97 , 98 ], vegetables [ 99 ], and legumes [ 100 ]. Similar to the antibacterial activity, earlier studies showed that B. thuringiensis isolates were less potent, in terms of antifungal activity, compared to other Bacillus species such as B. amyloliquefaciens and B. subtilis [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, in Algeria, the most injurious fungus species affecting palms are Fusarium oxysporum, the causal agent of ‘bayoud’, or Fusarium wilt [ 92 , 93 ], and Thielaviopsis paradoxa , the agent of the black scorch disease [ 94 , 95 ]. Different species of the genus Fusarium also affect cereals [ 2 , 96 ], forest trees (Aleppo Pine) [ 97 , 98 ], vegetables [ 99 ], and legumes [ 100 ]. Similar to the antibacterial activity, earlier studies showed that B. thuringiensis isolates were less potent, in terms of antifungal activity, compared to other Bacillus species such as B. amyloliquefaciens and B. subtilis [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…The oomycetes that were most common in this study ( Table 4 ) are also known to cause seedling diseases in forest nurseries, including taxa such as P. ultimum var. ultimum , P. heterothallicum [ 104 , 105 ] and P. spiculum [ 106 , 107 , 108 ]. Pythium spiculum was previously detected in the feeder roots and in the rhizosphere soil of declining oaks [ 109 ], but information on its pathogenicity to oaks is limited [ 106 ].…”
Section: Discussionmentioning
confidence: 99%
“…His results therefore have been published. Only later in the 2010s were published the first contributions of Algerian researchers (most often phytopathologists) reporting the observation of CFA taxa of which some new to Algeria (Corbière et al 2010;Lazreg 2015;Lazreg et al 2013Lazreg et al , 2016Benabdelkader and Ghechi 2013;Benabdelkader et al 2015;Rekad et al 2017;Smahi et al 2017).…”
mentioning
confidence: 99%